Rasionalitas Nilai-nilai Agama dalam Kehidupan Perempuan Pekerja Seks - Khodijah, Siti (Jurnal Sosiologi Agama, 2014)
One of the prostitutions to be found in Yogjakarta is in Sosrowijayan Kulon village. Geographically, the village is close with Malioboro shopping center and Yogyakarta train station. The prostitution place is much visited by consumers of sex. The existence of prostitution in the society of Sosrowijayan Kulon village makes sex workers have to mingle and follow various regulations applied by the local community. This research will explore rationalizing religious values and a model of action done by female sex workers. Data are obtained from primary sources and secondary technical resources by using interviews and observation. Data are to be analyzed by using the theory of rationalizing and type of action by Max Weber. The research found that religious values are understood by sex workers grouped into four types of rationality. First is rationality in religious activities. This can be viewed from sex workers who fail to perform a fast and keep working in Ramadan month. Second is substantive rationality. Religious values are seen from the sex workers perspective who gives alms, following formal religious gatherings (tahlilan/yasinan) and practices. Thirdly is formal rationality which is the responses of sex workers toward the rules of the village. The forth is theoretical rationality. It is employed to analyze the sex workers’ concept of religion.